Cost of postoperative ileus following colorectal surgery: A cost analysis in the Australian public hospital setting. (11th July 2022) - Traeger, Luke; Koullouros, Michalis; Bedrikovetski, Sergei; Kroon, Hidde M.; Thomas, Michelle L.; Moore, James W.; Sammour, Tarik
Abstract: Aim: Postoperative ileus (POI) following surgery results in significant morbidity, drastically increasing hospital costs. As there are no specific Australian data, this study aimed to measure the cost of POI after colorectal surgery in an Australian public hospital. Methods: A cost analysis was performed, for major elective colorectal surgical cases between 2018 and 2021 at the Royal Adelaide Hospital. POI was defined as not achieving GI‐2, the validated composite measure, by postoperative day 4. Demographics, length of stay and 30‐day complications were recorded retrospectively. Costings in Australian dollars were collected from comprehensive hospital billing data. Univariate and multivariate analyses were performed. Results: Of the 415 patients included, 34.9% ( n = 145) developed POI. POI was more prevalent in males, smokers, previous intra‐abdominal surgery, and converted laparoscopic surgery ( p < 0.05). POI was associated with increased length of stay (8 vs. 5 days, p < 0.001) and with higher rates of complications such as pneumonia (15.2% vs. 8.1%, p = 0.027). Total cost of inpatient care was 26.4% higher after POI (AU37, 690 vs. AU29, 822, p < 0.001). POI was associated with increased staffing costs, as well as diagnostics, pharmacy, and hospital services. On multivariate analysis POI, elderly patients, stoma formation, large bowel surgery, prolonged theatre time, complications and length of stay were predictive of increased costs ( p < 0.05). Conclusion: In Australia, POI is significantly associated with increased complications and higher costs due to prolonged hospital stay and increased healthcare resource utilisation. Efforts to reduce POI rates could diminish its morbidity and associated expenses, decreasing the burden on the healthcare system.